Assessment of Corrected QT Interval Prolongation in Liver Cirrhosis - Amir Shahzad, Irfan Younus, Muhammad Zahid Ali, Adnan Qadir, Amna Hafeez (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find out the frequency of corrected QT interval (QTc) prolongation in patients with liver cirrhosis. Study Design: Cross-sectional study. Place and Duration: The department of medicine, “Aziz Bhatti Shaheed Teaching Hospital”, Gujrat from April 2021 to October 2021. Methodology: A total of 150 patients of both genders aged 18-65 years having liver cirrhosis were included. Proper medical history and clinical examination were performed while electrocardiogram (ECG) was obtained to find out QT interval in all the patients. The frequency of QTc prolongation was recorded. Results: In a total of 150 patients, 66 (44.0%) were males and 84 (56.0%) females. The mean age was 48.67±16.67 years while the mean duration of cirrhosis was 4.71±1.18 years. Frequency of QTc prolongation was noted in 44 (29.3%) patients. Among ninty patients of liver cirrhosis with age more than 40 years, 31 (70.5%) had corrected QT interval prolongation (p=0.040). Among 84 female patients, there were 25 (56.8%) cases of corrected QT interval prolongation (p=0.047). Practical Implications: Potential cases of liver transplantation may be prioritized as per their risk of prolongation of QTc but further research is required in this regard. Conclusion: The frequency of QTc prolongation was quite high among patients of liver cirrhosis. Keywords: Cardiovascular disease, Electrocardiogram, liver cirrhosis, mortality, QT prolongation.